2021
DOI: 10.3390/plants11010002
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Profiling of Potassium Transport-Related Genes in Vigna radiata under Abiotic Stresses

Abstract: Potassium (K+) is one of the most important cations that plays a significant role in plants and constitutes up to 10% of plants’ dry weight. Plants exhibit complex systems of transporters and channels for the distribution of K+ from soil to numerous parts of plants. In this study, we have identified 39 genes encoding putative K+ transport-related genes in Vigna radiata. Chromosomal mapping of these genes indicated an uneven distribution across eight out of 11 chromosomes. Comparative phylogenetic analysis of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 98 publications
3
11
0
Order By: Relevance
“…4 ) [ 86 ]. Overall, our results conclude that MT application enhances Na + /K + homeostasis in cotton seedlings exposed to salt stress by changing the expressions of Na + and K + transporters [ 25 , 87 ].…”
Section: Discussionmentioning
confidence: 74%
“…4 ) [ 86 ]. Overall, our results conclude that MT application enhances Na + /K + homeostasis in cotton seedlings exposed to salt stress by changing the expressions of Na + and K + transporters [ 25 , 87 ].…”
Section: Discussionmentioning
confidence: 74%
“…The current study identified 37 potential genes of the K + transport system in M. indica genome. The number of PTGs is more or less similar in major plant groups represented by V. vinifera , Glycine max , Triticum aestivum , Vigna radiata , C. cajan , and A. thaliana ( Cuéllar et al., 2010 ; Isayenkov et al., 2011 ; Chen et al., 2017 ; Azeem et al., 2018 ; Azeem et al., 2021a ; Azeem et al., 2021b ; Ge et al., 2020 ; Siddique et al., 2021 ; Cai et al., 2021 ). It not only indicates the evolutionary conservation of PTGs in these plants but also predicts the existence of similar genetic mechanisms for K + in other fruit trees.…”
Section: Discussionmentioning
confidence: 99%
“…Salt stress is perceived as an excess of Na + that triggers an increase in cytosolic Ca 2+ levels and downstream signaling cascades. In this regard, a large number of transcripts annotated as cyclic nucleotide-gated channels (CNGCs) were upregulated in T48 (17) and T96 (4) compared to CK. Most of the CNGCs that were co-expressed in both salt treatments were downregulated in T96 compared to T48.…”
Section: Ca 2+ Signaling-related Expression Changes Between Salt Trea...mentioning
confidence: 99%
“…In addition to altering Ca 2+ levels, the increased Na + concentration also disrupts ion homeostasis (Na + /H + and/or Na + /K + exchange). To maintain the balance of ion concentrations, plants have evolved several molecular mechanisms such as activation/inactivation of Na + /H + antiporters [ 16 ], K + channels [ 17 ], calcineurin B-like proteins (CBLs), CBL-interacting protein kinases (CIPKs) [ 18 ], and calcium dependent protein kinases (CDPKs) [ 19 ]. The salt overly sensitive (SOS) regulatory pathway in plants also modulates the expressions/activities of Na + /H + antiporters to maintain ionic balance [ 14 , 20 ].…”
Section: Introductionmentioning
confidence: 99%